Deep Neural Network-Based Student Performance Prediction with Hessian-Free Optimization - Andy Irawan; Zainal Abidin; Mohammad Jamhuri (Jurnal Riset Mahasiswa Matematika, 2026)
Predicting student graduation predicates is important for academic monitoring and timely intervention in higher education. This study investigates graduation predicate prediction using deep neural networks under three feature-group settings: academic-only, non-academic-only, and combined academicnon-academic features. A multilayer perceptron with three hidden layers was trained using SGD with momentum, RMSProp, Adam, and a damped Hessian-free optimization procedure. Two tasks were considered: a four-class graduation predicate classification task and a binary risk-screening task in which Sufficient was treated as the positive risk class. The results show that the combined feature group achieved the best multiclass performance, with an accuracy of 0.8478 and a weighted F1-score of 0.8274. Hessian-free optimization consistently produced the best results across all feature-group scenarios, with the clearest gain appearing in the non-academic-only setting. In the additional risk-screening analysis, non-academic variables provided meaningful but limited predictive signal, and Major emerged as the strongest individual predictor. These findings show that combining academic and non-academic information improves graduation predicate prediction and that Hessian-free optimization is an effective training strategy for deep neural classification in educational data.